Neuroprotective effect of sacha inchi oil (Plukenetia volubilis L.) in an experimental model of epilepsy - Herrera-Calderon, Oscar (2019)
The authors thank Universidad Nacional Mayor de San Marcos for helping to support this research. Cesar Franco-Quino is a doctoral student studying an Epidemiological Researcher Doctorate at Universidad Peruana Cayetano Heredia under FONDECYT/ CIENCIAACTIVA scholarship EF033-235-2015 and supported by training grant D43 TW007393 awarded by Fogarti International Center of the US National Institutes of Health.